Mobile Solution for Child Abuse Reporting: Enhancing Accessibility and Protection through SI-ADU - Ardini, Pupung Puspa; Rawanti, Sri; Dwinanto, Arif; Setiyowati, Arbin Janu; Narosaputra, Dewo Agung Nugroho; Antara, Putu Aditya; Pupala, Branislav (Universitas Pendidikan Ganesha, 2024)
This study is motivated by the increasing cases of child abuse in Indonesia, with perpetrators often coming from close family members. This study to design an application that facilitates abuse victims in filing complaints. The research method used is Research & Development (R&D). Data collection techniques include field observation using observation sheets and interviews, a checklist for assessing abuse cases, questionnaires, expert assessment instruments, field notes, a questionnaire for evaluating the effectiveness of the application, and a checklist for assessing the application's usefulness. The subjects of this research are children, particularly those in early childhood. The result of this research is the design of a mobile-based child protection application, SI-ADU, which can be accessed by children or parents to file complaints. The implications of this study suggest that it can help the Gorontalo local government reduce the number of child abuse cases by up to 19% since the pilot testing was conducted. The easy access and use of techniques to defend or protect oneself from abuse, as well as rapid mitigation for child victims of abuse through smartphones, can contribute to improving safety and preventing violence within children's communities. The conclusion of this study is that the SI-ADU application can be an effective solution in addressing child abuse by providing victims with quick and easy access to report abuse cases and involve authorities in the handling of these cases.